2014
DOI: 10.1155/2014/467235
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Optimization of a Counterrotating Type Pump-Turbine Unit Operated at Turbine Mode

Abstract: A multiobjective optimization for improving the turbine output and efficiency of a counterrotating type pump-turbine unit operated at turbine mode was carried out in this work. The blade geometry of both the runners was optimized using a hybrid multiobjective evolutionary algorithm coupled with a surrogate model. Three-dimensional Reynolds-averaged Navier-Stokes equations with the shear stress transport turbulence model were discretized by finite volume approximations and solved on hexahedral grids to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Counter-rotating type pump-turbine. 6 and 81.26%, respectively, in turbine mode. Detailed specifications for the pump and turbine modes are given in Tables 1 and 2, respectively.…”
Section: Counter-rotating Type Pump-turbinementioning
confidence: 94%
See 1 more Smart Citation
“…Counter-rotating type pump-turbine. 6 and 81.26%, respectively, in turbine mode. Detailed specifications for the pump and turbine modes are given in Tables 1 and 2, respectively.…”
Section: Counter-rotating Type Pump-turbinementioning
confidence: 94%
“…[1][2][3][4] Thus far, many kinds of studies have been conducted on counter-rotating type pump-turbines to understand the mechanisms, internal flow characteristics, and hydrodynamic performance characteristics. [5][6][7][8][9] Kim et al 6,7 enhanced the turbine efficiency of a counter-rotating type pump-turbine unit being operated in turbine mode using various optimization techniques. The results showed that the turbine efficiency was improved by 2.68% at the best efficiency point as compared with the reference design.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted on the counterrotating-type pump-turbine unit to increase the performance and understand the internal flow mechanism of the unit by experimental and simulation methods [1][2][3][4][5]. In addition, Murakami and Kanemoto [6] studied the tandem impellers of the counter-rotating type pump unit operated in the turbine mode.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [2] utilized the CFD to study the incompressible viscous flows of mixed flow pumps in the incidents of power failure. De et al [3] conducted studies utilizing the CFD and DOE for the optimization of single-blade impellers; Kim et al [4] conducted studies utilizing the CFD to improve the performance of counter-rotating type pump-turbine units; Cho et al [5] designed axial-type fans using optimization methods based on the gradient method; and Kim et al [6] studied the shape optimization of mixed-flow pumps' impellers and diffusers through the DOE.…”
Section: Introductionmentioning
confidence: 99%